2013
DOI: 10.1155/2013/581945
|View full text |Cite
|
Sign up to set email alerts
|

Emissions and Fuel Consumption Modeling for Evaluating Environmental Effectiveness of ITS Strategies

Abstract: Road transportation is a major fuel consumer and greenhouse gas emitter. Recently, the intelligent transportation systems (ITSs) technologies, which can improve traffic flow and safety, have been developed to reduce the fuel consumption and vehicle emissions. Emission and fuel consumption estimation models play a key role in the evaluation of ITS technologies. Based on the influence analysis of driving parameters on vehicle emissions, this paper establishes a set of mesoscopic vehicle emission and fuel consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…A linha preta corresponde à função de correlação do consumo de combustível e velocidades para os ônibus convencionais proposta. Contudo, estudos experimentais (ANTUNES, 2009;FREY et al, 2007;SIMÕES;CUNHA, 2006) indicam que é preciso existir uma correlação mais universal que contemple as velocidades mais elevadas, mas especialmente as velocidades abaixo de 15 km/h (Figura 2). A equação (1) representa a correlação de consumo para todas as condições de velocidades, proposta pelo estudo, para ICB.…”
Section: Consumo De Combustívelunclassified
“…A linha preta corresponde à função de correlação do consumo de combustível e velocidades para os ônibus convencionais proposta. Contudo, estudos experimentais (ANTUNES, 2009;FREY et al, 2007;SIMÕES;CUNHA, 2006) indicam que é preciso existir uma correlação mais universal que contemple as velocidades mais elevadas, mas especialmente as velocidades abaixo de 15 km/h (Figura 2). A equação (1) representa a correlação de consumo para todas as condições de velocidades, proposta pelo estudo, para ICB.…”
Section: Consumo De Combustívelunclassified
“…Due to the high volumes of vehicles in urban areas a vast body of mobility research has been developed to measure and evaluate the pollutants exhaust emissions from vehicles (Boriboonsomsin et al, 2012, Song et al, 2013. As the reduction and estimation of these emissions will led to a better quality of life in urban areas.…”
Section: Emission Measurementmentioning
confidence: 99%
“…A portable emissions measurement system was used by authors concluded that standards for NO 2 and PM 2.5 as well as the annual emission limit for PM 10 are difficult to attain. Song, Yao, et al (2013) and risk to local environments. It was found that the heavy metal concentrations and their ecological risk indices decreased exponentially with increased roadside distance, with a moderate level of ecological risk within a 10 m roadside distance.…”
Section: Concentrations Of 30 Volatile Organic Compoundsmentioning
confidence: 99%